Research progress on the role and mechanism of miR-671 in bone metabolism and bone-related diseases - Wang, Shaotai; Hu, Min; Song, Dongsheng; Tang, Linjun; Jiang, Huan (Frontiers in Oncology, 2023)
Bone metabolism consists of bone formation and resorption and maintains a dynamic balance in vivo. When bone homeostasis is broken, it can manifest as osteoarthritis (OA), rheumatoid arthritis (RA), osteosarcoma (OS), etc. MiR-671, an important class of non-coding nucleotide sequences in vivo, is regulated by lncRNA and regulates bone metabolism balance by regulating downstream target proteins and activating various signaling pathways. Based on the structure and primary function of miR-671, this paper summarizes the effect and mechanism of miR-671 in bone-related inflammation and cancer diseases, and prospects the application possibility of miR-671, providing reference information for targeted therapy of bone-related disorders.